2012
DOI: 10.1021/cm3000427
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Method-Assisted Ab Initio Study of Olivine-Type LiMXO4 (Main Group M2+–X5+ and M3+–X4+) Compositions as Potential Solid Electrolytes

Abstract: Lithium-ion conductive solid oxide electrolytes are receiving increasing attention for the development of highperformance all-solid state rechargeable Li-ion batteries. In this study, we report an effective search method that uses a combination of ab initio calculations and multivariate analysis to find potential solid oxide electrolyte materials with low Li-ion hopping energies (EAs) among 66 olivine-type oxides with an ordered structure LiMXO 4 (main group M 2+ −X 5+ , M 3+ −X 4+ ). The ionic size of M, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 35 publications
7
65
0
1
Order By: Relevance
“…Using high‐throughput computations and ML, Jalem et al have studied vacancy‐mediated Li ion migration and the Li hopping energies in olivine LiMXO 4 (main group M 2+ –X 5+ , M 3+ –X 4+ ) and tavorite LiMTO 4 F (M 3+ –T 5+ , M 2+ –T 6+ ) cathodes. In olivine LiMXO 4 , the authors revealed that the degree of M octahedron distortion increases with ionic size of the M cation, which in turn results in an energy‐penalizing local lattice distortion around the migration pathway and a higher migration barrier (see Figure 5 a).…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Using high‐throughput computations and ML, Jalem et al have studied vacancy‐mediated Li ion migration and the Li hopping energies in olivine LiMXO 4 (main group M 2+ –X 5+ , M 3+ –X 4+ ) and tavorite LiMTO 4 F (M 3+ –T 5+ , M 2+ –T 6+ ) cathodes. In olivine LiMXO 4 , the authors revealed that the degree of M octahedron distortion increases with ionic size of the M cation, which in turn results in an energy‐penalizing local lattice distortion around the migration pathway and a higher migration barrier (see Figure 5 a).…”
Section: Applicationmentioning
confidence: 99%
“…The blue data points represent experimental data in ICSD. Reproduced with permission . Copyright 2012, American Chemical Society.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this path dimensionality has been observed in Li-based olivine frameworks although there is a difference in terms of the intermediate position between two adjacent crystallographic sites. [28][29][30][31] In the tavorite structure, the intermediate position it is located at an octahedral site while in the olivine structure, is located at a tetrahedral site. In the next sections, the different factors that affect ME will be discussed.…”
Section: Li/na Ion Transport Pathwaysmentioning
confidence: 99%
“…However, T-O bonding is determined to be strongly covalent as indicated by the relatively lower values of the Born charges than the nominal ones. 28 This T-O covalency should allow for a reduced interaction between the mobile A cation and the lattice along paths 2 and 3, and should lead to a lower ME; the electron cloud from the oxide ion in BO 4 F 2 is drawn away towards TO 4 (Figs. 2b-2d), thus effectively minimizing the energy penalty for electron cloud overlap at the transition site for paths 2 and 3.…”
Section: Li/na Ion Transport Pathwaysmentioning
confidence: 99%